2018
DOI: 10.1097/gox.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Positive Postdebridement Cultures on Local Muscle Flap Reconstruction of the Lower Extremity

Abstract: Background:Local muscle flaps are a reconstructive option for wound coverage in the distal lower extremity, particularly in high-risk patients who are poor candidates for free tissue transfer. At our institution, chronic and infected wounds are managed with serial debridement before definitive reconstruction. There is a paucity of data on optimal timing for reconstruction in this patient population. This study investigates the relationship of positive postdebridement cultures (PDC) and wound closure rates at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The management of infected wounds that also require hardware retention is challenging. The results of several investigations have suggested that positive wound culture is an independent predictor of hardware salvage failure and associated flap failure [ 25 27 ]. In our study group, 80% of patients had positive wound cultures, and 66.7% of them required hardware salvage.…”
Section: Discussionmentioning
confidence: 99%
“…The management of infected wounds that also require hardware retention is challenging. The results of several investigations have suggested that positive wound culture is an independent predictor of hardware salvage failure and associated flap failure [ 25 27 ]. In our study group, 80% of patients had positive wound cultures, and 66.7% of them required hardware salvage.…”
Section: Discussionmentioning
confidence: 99%
“…Positive postdebridement cultures and smoking have been shown as strong predictors of wound closure failure among local flaps in lower extremity reconstruction. 21 Aggressive debridement and wound bed preparation serve as critical initial steps to guarantee minimal complications with a high local flap success rate in managing both acute and chronic wounds. [22][23][24] Given the high-acuity setting of a level 1 trauma center, our patient population lacks the preoperative medical optimization afforded in the outpatient setting when smoking cessation, blood pressure management, and proper glycemic control would be optimized; furthermore, preoperative angiography has proven to be of added benefit, especially for patients with diabetes mellitus or peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cigarette smoking is a known vasoconstriction, which can compromise blood supply and portent infectious risk. Positive postdebridement cultures and smoking have been shown as strong predictors of wound closure failure among local flaps in lower extremity reconstruction 21 . Aggressive debridement and wound bed preparation serve as critical initial steps to guarantee minimal complications with a high local flap success rate in managing both acute and chronic wounds 22–24 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the local blood supply to the defect through vascularization also minimizes risk of infection via increased perfusion of protective immune system elements and/or systemically administered antibiotics ( 25 ). Indeed, proper site preparation is vital for successful closure of chronic defects with positive post-debridement cultures being a proven predictor of failure of flap closure ( 26 ), as such our procedure included aggressive debridement and removal of chronic defective tissues. Additionally, placement of ECM graft material in the defect bed may provide occlusion of dead space between the flap and underlying soft tissues.…”
Section: Discussionmentioning
confidence: 99%